Effects of creatine and sodium bicarbonate coingestion on multiple indices of mechanical power output during repeated Wingate Tests in trained men - Griffen, C.; Rogerson, D.; Ranchordas, M.; Ruddock, A. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
This study investigated the effects of creatine and sodium bicarbonate coingestion on mechanical power during repeated sprints. Nine well-trained men (age = 21.6 ± 0.9 yr, stature = 1.82 ± 0.05 m, body mass = 80.1 ± 12.8 kg) participated in a double-blind, placebo-controlled, counterbalanced, crossover study using six 10-s repeated Wingate tests. Participants ingested either a placebo (0.5 g·kg-1 of maltodextrin), 20 g·d-1 of creatine monohydrate + placebo, 0.3 g·kg-1 of sodium bicarbonate + placebo, or coingestion + placebo for 7 days, with a 7-day washout between conditions. Participants were randomized into two groups with a differential counterbalanced order. Creatine conditions were ordered first and last. Indices of mechanical power output (W), total work (J) and fatigue index (W·s-1) were measured during each test and analyzed using the magnitude of differences between groups in relation to the smallest worthwhile change in performance. Compared with placebo, both creatine (effect size (ES) = 0.37-0.83) and sodium bicarbonate (ES = 0.22-0.46) reported meaningful improvements on indices of mechanical power output. Coingestion provided small meaningful improvements on indices of mechanical power output (W) compared with sodium bicarbonate (ES = 0.28-0.41), but not when compared with creatine (ES = -0.21-0.14). Coingestion provided a small meaningful improvement in total work (J; ES = 0.24) compared with creatine. Fatigue index (W·s-1) was impaired in all conditions compared with placebo. In conclusion, there was no meaningful additive effect of creatine and sodium bicarbonate coingestion on mechanical power during repeated sprints.